INFLUENCE OF MANAGEMENT ACCOUNTING PRACTICES ON MSMEs FIRMS PERFORMANCE - Yoseph Agus Bagus Budi N.; Dewi Wulansari; Harti Budi Yanti (International Journal of Contemporary Accounting, 2023)
The motivation behind this work was to explore the management accounting practices in Small Medium Enterprices (SMEs) in Indonesia, using primary data captured across Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek). The research compiled primary data using personally administered questionnaries. Using 185 completed questioneries from respondents. PLS was used to perform analysis of the research, with uniqnes of financial resources and technological literacy as moderating variables. This research indicate three interesting findings that are in line with previous researchs. The budgeting system, performance measurement system and strategic management accounting influence firm performance positively. While the technology literacy and financial resources fail to strengthen their influence towards firm performance. Costing system and decision support system do not influence firm performance, and further technology and financial resource were not able to make the influence strengthened.